Tricuspid valve repair concomitant with the Norwood operation among babies with hypoplastic left heart syndrome. (13th February 2022) - Wamala, Isaac; Friedman, Kevin G; Saeed, Mossab Y; Gauvreau, Kimberlee; Gellis, Laura; Borisuk, Michele; Kaza, Aditya; Emani, Sitaram; del Nido, Pedro J; Baird, Christopher W
Abstract: OBJECTIVES: Among patients with hypoplastic left heart syndrome (HLHS), tricuspid valve regurgitation (TR) portends a poor prognosis. Our goal was to describe the outcomes of tricuspid valve reconstruction (TVR) concomitant with the Norwood operation and using two-dimensional echocardiography and evaluate the structural factors associated with successful functional correction. METHODS: We performed a retrospective, single-centre study of patients with HLHS undergoing TVR at the time of the Norwood operation. Structural echocardiographic parameters were compared between patients with successful correction (≤ mild TR) and those with ≥ moderate regurgitation at discharge. Preoperative dimensions of matched HLHS controls with ≤ trivial TR were used as a reference. RESULTS: Of 205 patients with HLHS undergoing the Norwood operation, 18 patients had a concomitant TVR. Ten (56%) patients had an improved TR grade postoperatively, 8 (44%) of whom had ≤ mild TR at discharge. Improvement in TR grade ( P  = 0.001) and having ≤ mild TR at discharge ( P  = 0.011) were associated with an improved reintervention and TR-free survival. Patients with successful functional correction had smaller preoperative tricuspid annulus lateral dimensions ( P  = 0.023), tricuspid valve area ( P  = 0.007) and right ventricle mid-width ( P  = 0.064). Preoperatively, the successful TVR cases tended to have had higher anterior leaflet excursion (80 ± 20 vs 55 ± 11, P  = 0.010), and a higher proportion of anterior leaflet prolapse (63% vs 10%, P  = 0.043) compared to cases where TVR was not successful. CONCLUSIONS: Patients with HLHS with significant tricuspid regurgitation undergoing the stage 1 operation were more likely to have successful concomitant tricuspid valve repair if they had less tricuspid annular dilation, less-severe RV enlargement and predominantly anterior leaflet prolapse. Successful tricuspid valve repair was associated with improved mid- and long-term outcomes. Abstract : Staged treatment has led to improved survival and quality of life among patients with hypoplastic left heart syndrome (HLHS) [1].